Simulation training using WhatsApp (Sim-thru-WhatsApp) improves doctors' confidence in endocrine and diabetes case management. (2020) - Chen, Wentin; Kempegowda, Punith; Melson, Eka; Davitadze, Meri; Aftab, Manal; Ooi, Emma
No abstract available